FIRST RECORD OF CHAETOMORPHA MINIMA (COLLINS & HERVEY, 1917) ASSOCIATED WITH THE MANGROVE STANDS IN THE SANDSPIT BACKWATERS, KARACHI – PAKISTAN - Qadeer Mohammad Ali; Quratulan Ahmed; Fikrat. M. Hassan; Farhad. H. Aziz (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2024)
This research paper report and discuss the first record of Chaetomorpha minima from Pakistan. The study sheds light on the fine aspects of the surface and interior structures of the species thorough morphological assessment of the taxonomic aspects. The cosmopolitan genus Chaetomorpha is commonly known as “Spaghetti algae”. It is a green alga belongs to the family Cladophoraceae. The specimen was collected from nutrient-rich, shallow environment of Sandspit backwaters mangrove area which is connected with the Arabian Sea through Manora Channel. Mangrove forest comprises of only one species Avicennia marina andprovides good feeding, sheltering and breeding ground for many species of birds giving significant importance by providing a representative wetland ecosystem close to the mega city.